Household chaos as a context for intergenerational transmission of executive functioning. (July 2017) - Brieant, Alexis; Holmes, Christopher J.; Deater-Deckard, Kirby; King-Casas, Brooks; Kim-Spoon, Jungmeen
Abstract: Executive functioning (EF) may be transmitted across generations such that strengths or deficiencies in parent EF are similarly manifested in the child. The present study examined the contributions of parent EF and impulsivity on adolescent EF, and investigated whether household chaos is an environmental moderator that alters these transmission processes. American adolescents (N = 167, 47% female, 13–14 years old at Time 1) completed behavioral measures of EF and reported household chaos at Time 1 and one year later at Time 2. Parents completed behavioral measures of EF and self-reported impulsivity at Time 1. Results indicated that lower parent EF at Time 1 predicted lower adolescent EF at Time 2 (controlling for adolescent EF and IQ at Time 1), but only in the context of high household chaos. Findings suggest that household chaos may be a risk factor that compounds influences of poor parent EF and compromises adolescent EF development.